Effect of biochar amendment on sorption and leaching of nitrate, ammonium, and phosphate in a sandy soil - Yao, Ying; Gao, Bin; Zhang, Ming; Inyang, Mandu; Zimmerman, Andrew R. (Chemosphere (Oxford), 2012)
► Effect of biochar on the leaching of nutrients in soils is not uniform. ► Sorption of nutrients on biochar varies by biochar and nutrient type. ► Nutrient sorption characteristics should be studied prior to biochar application. When applied to soils, it is unclear whether and how biochar can affect soil nutrients. This has implications both to the availability of nutrients to plants or microbes, as well as to the question of whether biochar soil amendment may enhance or reduce the leaching of nutrients. In this work, a range of laboratory experiments were conducted to determine the effect of biochar amendment on sorption and leaching of nitrate, ammonium, and phosphate in a sandy soil. A total of thirteen biochars were tested in laboratory sorption experiments and most of them showed little/no ability to sorb nitrate or phosphate. However, nine biochars could remove ammonium from aqueous solution. Biochars made from Brazilian pepperwood and peanut hull at 600°C (PH600 and BP600, respectively) were used in a column leaching experiment to assess their ability to hold nutrients in a sandy soil. The BP600 biochar effectively reduced the total amount of nitrate, ammonium, and phosphate in the leachates by 34.0%, 34.7%, and 20.6%, respectively, relative to the soil alone. The PH600 biochar also reduced the leaching of nitrate and ammonium by 34% and 14%, respectively, but caused additional phosphate release from the soil columns. These results indicate that the effect of biochar on the leaching of agricultural nutrients in soils is not uniform and varies by biochar and nutrient type. Therefore, the nutrient sorption characteristics of a biochar should be studied prior to its use in a particular soil amendment project.